The Influence of Student Team Achievement Division (STAD) Strategy and Learning Styles toward Reading Comprehension Achievement of the Tenth Grade Students of State Islamic Senior High School Number 1 of Palembang - Rika Puspita Sari; Indawan Syahri; Tahrun Tahrun (Universitas PGRI Palembang, 2018)
AbstractThis research was investigate the influence of STAD Strategy and Learning Styles toward reading comprehension achievement to the Tenth grade students of The State Islamic Senior High School Number 1 of Palembang. In carrying out this research, the writer selected two groups randomly: The experimental group and the control groups with six subjects each group and writer used factorial design. In analyzing the data, writer used statistic analysis and two-way ANOVA in SPSS15. Based on the result of calculating using independent t-test, it was found as follows: First, There was a significant difference in reading comprehension achievement between students who have visual learning styles and those who have auditory learning style taught using by STAD of State Islamic Senior High School Number 1 of Palembang. Second, There was a significant difference in reading comprehension achievement between studentswho have visual learning styles and those who have auditory learning style taught using by conventional class of State Islamic Senior High School Number 1 of Palembang. Third, There was a significant difference in reading comprehension achievement between students who have visual learning styles and those who have auditory learning style taught using by STAD and conventional class of State IslamicSenior High School Number 1 of Palembang. Fourth, there were significant interaction effects of STAD and learning styles toward reading comprehension achievement of State Islamic Senior High School Number 1 of Palembang.Keywords : STAD, Learning Styles, Reading Comprehension Achievement